Evaluation of biofortified spring wheat genotypes for yield and micronutrients - Chatrath, Ravish; Gupta, Vikas; Parkash, Om; Singh, Gyanendra Pratap (Applied and Natural Science Foundation, 2018)
Advanced wheat genotypes were tested for agronomic as well as grain iron and zinc content traits. The analysis of variance indicated variation for all traits except iron (Fe) and zinc (Zn). The grain Fe content ranged from 39-58 mg/kg whereas grain Zn ranged from 32-47 mg/kg among the tested lines. A significant positive correlation (0.45) was observed between grain Fe and Zn content. There was no association between yield and grain Fe and Zn content indicating that improvement in these micronutrients will not have any undesirable affect on yield. The data was further analysed for principal component analysis and genotype by trait association. The first five principal components viz., PC1 (0.3149), PC2 (0.2198), PC3 (0.1461), PC4 (0.10) and PC5 (0.0923) accounted for 0.87 of the total variation. The major traits contributing to the PC1 are days to heading, days to maturity, grain iron content and yield. The cluster analysis revealed significant variation among the tested germplasm thus providing opportunities for increasing the micronutrient content along with yield through hybridization with high micronutrient content lines.